International Classification of Functioning, Disability and Health (ICF) in medical certification of disability - Cichońska, Dominika; Marczak, Michał; Raczkiewicz, Anna; Sierocka, Aleksandra (Polish Journal of Public Health, 2009)
Introduction. Health jurisdiction in disability is a wide concept including jurisdiction about health, ability to work, about disability. The aim of the study is presenting an opportunity of using International Classifi cation of Functioning, Disability and Health (ICF) in medical certifi cation exemplifi ed by osteoporosis. The classifi cation defi nes health-related abilities of an individual, functioning of the organism and the scope of participation in society. The classifi cation allows for perception of a human as a whole, including their problems in communication with environment. Material and methods. Questionnaire is the research tool, designed on ICF Core Sets Validation Study, fi lled up by 50 patients from Military Medical Institute in Warsaw. Results. The following logical system is therefore suggested: for the needs of creation of a taxonomy differentiating the conditions of health and its loss (or a disease), the ICF platform combined with the ID-10 is used, superimposing a transformation to the space of possible formal therapies, medical interventions, preventive activities and population diagnoses. Utilisation of the ICF classifi cation can have a signifi cant infl uence on the unifi cation and objectifi cation of diagnostics, certifi cation and making decisions on turning points in the choice of medical procedures and therapies and on the whole, broadly understood healthcare system.